Assessment of the Service Performance of Zakah Institutions in Gombe Metropolis, Nigeria - Sulaiman, Sagir Muhammad; Magaji, Mohammed; Rabiu, Warshu Tijjani (International Journal of Islamic Economics and Finance (IJIEF), 2021)
Zakah is an important tool in Islamic economic system, it plays a crucial role in reducing some social and economic problems such as poverty, unemployment, indebtedness and inequitable redistribution of income in the Muslim communities. The Zakah institutions in Gombe metropolis are said to practice favouritism and unfair service quality and distribution of Zakah funds among recipients. The main objective of this study is to empirically examine perception of the Zakah recipients towards the services provided by the institutions. This study adopted descriptive survey design approach. PLS-SEM is employed to test the hypothesized model of the study. The result reveals that reliability, responsiveness and assurance significantly affect performance of Zakah institutions but tangibility and empathy were found to be insignificant. The study recommends the need for Zakah institutions in Gombe metropolis to consider improving the tangibles and empathy dimensions of service quality. The study also recommends the need to concentrate on the antecedents of service quality as it will assist Zakah institutions to improve performance. Lastly, the study suggests the establishment of Zakah board that will serve as regulatory body in charge of supervising the activities of private Â Zakah institutions in Gombe state.